(untitled) (Community Based Medical Journal, 2014)
Knowledge on sexually transmitted disease like HIV/AIDS can affect and help in reducing the incidence and number of cases of the disease in the community. The present study makes an attempt to assess the knowledge on mode of transmission and prevention of HIV/AIDS among the floating sex workers in some selected areas of Dhaka city. A descriptive type of cross-sectional study was conducted for a period of six months from January to June 2009, in Drop in centers in some selected areas of Dhaka city. Data were collected from 90 floating sex workers to find their knowledge about HIV/AIDS. Of the 90 respondents, 88 (97.8%) respondents had heard of HIV/AIDS. Majority of them (52, 57.9%) were got knowledge on HIV/AIDS from NGO workers followed by 13 (14.4%) from radio and 12(13.3%) from television. Most of the respondents (74, 82.2%) knew that HIV could be transmitted by unsafe sex with a known case of AIDS. Regarding prevention of HIV/AIDS, 73(81.1%) respondents knew that use of condom was a way of prevention of AIDS. Majority (51, 56.7%) scored average knowledge on transmission and prevention of HIV/AIDS. Government and non-government organizations and media can play effective role to make people aware of HIV/AIDS particularly the high risk groups. CBMJ 2014 January: Vol. 03 No. 01 P: 41-45